PERLAKUAN AKUNTANSI DAN TELAAH BAGI HASIL PRODUK MUDHARABAH BERDASARKAN PSAK 105 PADA PT BANK SULSELBAR CABANG SYARIAH MAKASSAR - Indrawan Azis (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This research used descriptive approach.. this type of data used in the from of data a qualitative with the data in the form of data, primary and the secondary. Data was collected by interview and documentation. The data analysis technique comsist of several stages, they are 1) analysis for the product mudharabah; 2) describe the types of financing products offered by PT Bank Sulselbar Cabang Syariah Makassar; 3) Describe the application of financing in PT Bank Sulselbar Cabang Syariah Makassar; 4) Analyzing above accounting treatment of mudharabah financing based on PSAK No. 105 at PT Bank Sulselbar Cabang Syariah Makassar include the recognition, measurement, presentation and disclosure. The result showed that the capital work mitra Ib is financing product offered by PT Bank Sulselbar Cabang Syariah Makassar with Al-Mudharabah Wal Murabahah contract. PT Bank Sulselbar Cabang Syariah Makassar has implemented PAPSI 2013 entirely on the products of mudharabah financing right from the recognition, measurement, presentation, until the disclosure. But PSAK No. 105 PT Bank Sulselbar Cabang Syariah Makassar has not been fully able to implement the product of mudharabah financing, therefore PT Bank Sulselbar Cabang Syariah Makassar should disclose the report of zakat and charity fund